The Effect of Profitability, Leverage, and Liquidity on Company Value with Dividend Policy as a Moderating Variable - Putri, Dewi Diana; Hidayat, Rendra Arief (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study analyzes the effect of profitability, liquidity, and leverage on firm value and evaluates the role of dividend policy as a moderating variable. This quantitative study uses data from 21 textile and garment sub-sector manufacturing companies on the IDX for the 2019–2023 period selected through purposive sampling. The analysis was conducted using multiple linear regression and MRA using SPSS 30. The results showed that profitability, leverage, and liquidity had a significant positive effect on firm value. Dividend policy moderates the effect of profitability and liquidity, but not leverage.